Becoming Origin(al): Deterritorialization and Postcolonial Theory from the Caribbean - Brown, William Christopher (FORUM: University of Edinburgh Postgraduate Journal of Culture & the Arts, 2005)
"Becoming Origin(al)" alludes to Gilles Deleuze and Félix Guattari's idea of "becoming minor" in Kafka: Toward a Theory of Minor Literature. This article will discuss Deleuze and Guattari's ideas in full, but the article will first set out to provide a context for thinking about postcolonial theory in relation to the Caribbean, with specific reference to Edouard Glissant's Caribbean Discourse and Jean Bernabé, Patrick Chamoiseau, and Raphaël Confiant's In Praise of Creoleness.